2020
DOI: 10.3389/fcell.2020.550543
|View full text |Cite
|
Sign up to set email alerts
|

SERPINA1 Gene Promoter Is Differentially Methylated in Peripheral Blood Mononuclear Cells of Pregnant Women

Abstract: SERine Protein INhibitor-A1 (SERPINA1) is an inducible blood cell gene coding for alpha1-antitrypsin (AAT), a plasma protease inhibitor whose circulating levels are raised during inflammation, infection and advanced pregnancy. DNA methylation has been suggested to play a role in SERPINA1 gene expression regulation in peripheral blood mononuclear cells (PBMCs). The methylation status of SERPINA1 in PBMCs is unknown. The aim of this study was to evaluate the methylation profile of the SERPINA1 promoter in PBMC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…HDAC is a family of key epigenetic factors that regulates the expression of genes in concert with DNA methylation and miRNA expression [ 120 , 121 , 122 , 123 , 124 ]. In the TGF-β signaling pathway, the HDAC4/5 complex binds the nuclear phosphorylated R-SMAD SMAD2/3 to repress RUNX2 expression, resulting in osteoblast differentiation inhibition [ 125 ].…”
Section: Osteogenic Differentiation By Mirna Regulationmentioning
confidence: 99%
“…HDAC is a family of key epigenetic factors that regulates the expression of genes in concert with DNA methylation and miRNA expression [ 120 , 121 , 122 , 123 , 124 ]. In the TGF-β signaling pathway, the HDAC4/5 complex binds the nuclear phosphorylated R-SMAD SMAD2/3 to repress RUNX2 expression, resulting in osteoblast differentiation inhibition [ 125 ].…”
Section: Osteogenic Differentiation By Mirna Regulationmentioning
confidence: 99%
“…Statistical analyses were performed using the GraphPad Prism for Windows (version 6.0, GraphPad, California, USA) [48,49]. For mRNA, fold change was calculated by the 2 -ΔΔCt method and represented in Log 2 scale, using HPV-negative samples as controls [31].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…SERPINA1 is also an inducible gene upon activating its inflammation-responsive promoter in hepatocytes, monocytes and macrophages [ 7 , 16 , 17 ]. High levels of circulating AAT, fourfold to sixfold higher than baseline levels, are present during the course of inflammation, infections and late pregnancy [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study we have performed a comprehensive assessment of SERPINA1 gene promoter methylation profile in peripheral blood mononuclear cells (PBMCs) from healthy subjects [ 21 ]. We showed that SERPINA1 gene promoter is hypermethylated in healthy individuals, such as blood donors, but hypomethylated in pregnant women at the third trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation